Binding-protein-dependent alanine transport in Rhodobacter sphaeroides is regulated by the internal pH. - Abee, T (1989)
The properties of an L-alanine uptake system in Rhodobacter sphaeroides were studied and compared with those of H+/lactose symport in R. sphaeroides 4P1, a strain in which the lactose carrier of Escherichia coli has been cloned and functionally expressed (F. E. Nano, Ph.D. thesis, University of Illinois, Urbana, 1984). Previous studies indicated that both transport systems were active only when electron transfer took place in the respiratory or cyclic electron transfer chain, while uptake of L-alanine also required the presence of K+ (M. G. L. Elferink, Ph.D. thesis, University of Groningen, Groningen, The Netherlands, 1986). The results presented in this paper offer an explanation for these findings. Transport of the nonmetabolizable L-alanine analog 2-alpha-aminoisobutyric acid (AIB) is mediated by a shock-sensitive transport system. The apparently unidirectional uptake of AIB results in accumulation levels which exceed 7 x 10(3). The finding of L-alanine-binding activity in the concentrated crude shock fluid indicates that L-alanine is taken up by a binding-protein-dependent transport system. Transport of the nonmetabolizable lactose analog methyl-beta-D-thiogalactopyranoside (TMG) by the lactose carrier under anaerobic conditions in the dark was observed in cells and membrane vesicles. This indicates that the H+/lactose symport system is active without electron transfer. Uptake of AIB, but not that of TMG, is inhibited by vanadate with a 50% inhibitory concentration of 50 microM, which suggests a role of a phosphorylated intermediate in AIB transport. Uptake of TMG and AIB is regulated by the internal pH. The initial rates of uptake increased with the internal pH, and and pKa values of 7.2 for TMG and 7.8 for AIB. At an internal pH of 7, no AIB uptake occurred, and the rate of TMG uptake was only 30% of the rate at an internal pH of 8. In a previous study, we found that K+ plays an essential role in regulating the internal pH (T. Abee, K. J. Hellingwerf, and W. N. Konings, J. Bacteriol. 170:5647-5653, 1988). The dependence of solute transport in R. sphaeroides on both K+ and activity of an electron transfer chain can be explained by an effect of the internal pH, which subsequently influences the activities of the lactose-and binding-protein-dependent L-alanine transport system.